The Influence Of Positive Self-Talk On Motivation To Heal In Prisoners With Drug Abuse Cases In Prisons Class Ii B Polewali West Sulawesi - Aeni, Nurul; Yosep, Iyus; Sriati, Aat (Jurnal Kesehatan Manarang, 2024)
The prevalence of convicts who abuse drugs continues to increase. Motivation is one of the main factors that hinders the recovery process. The role of nurses is crucial in handling efforts to improve recovery. The nursing intervention that can be carried out is Positive Self-Talk. Positive Self-Talk provides encouragement and motivation to make changes to individuals. The aim of the research is to determine the effect of positive self-talk on motivation to recover in prisoners who are victims of drug abuse. The research method used is quasi experimental with a pre-test and post-test with control group research design. The number of samples was 80 respondents with 40 respondents in the control group and 40 respondents in the intervention group who were drug users in Class II B Prison. The research was conducted over 7 days with 14 meetings and involved daily self-reports twice a day, in the morning and evening, using the University of Rhode Assessment Scale (URICA) questionnaire. Data analysis used univariate tests and bivariate tests, namely the Wilcoxon test and the Mann-Whitney test. The pre-test showed that 67.5% of the control group and 65% of the intervention group were in the precontemplation stage. However, the post-test showed significant changes with 57.5% of the control group moving to the contemplation stage, while 75.5% of the intervention group were at that stage. The results of the Wilcoxon and Mann-Whitney U tests strengthened significant differences between groups (p-value < 0.001). positive self-talk has a significant influence on motivation in drug abuse convicts. For further research to measure the precision of the effectiveness of the Positive Self-Talk intervention, it can be done by increasing the duration of the intervention. The recommendation is to integrate positive self-talk as an important part of the rehabilitation program by providing training to counselors in its application.